Guide to Library User Needs Assessment for Integrated Information Resource: Management and Collection Development - Biblarz, Dora; Bosch, Stephen; Sugnet, Chris (Rowman & Littlefield Publishers, 2001)
Applicable for all types of libraries. Needs assessment can be defined as the process of using one or more techniques to collect and analyze data on library users or potential users. The guide includes the methodology and techniques for carrying out needs assessment projects, ranging from short-term assessments to long-term research or comprehensive collection assessments. Various types of data, techniques, and methodology are described, as are associated pointers and pitfalls.